Analysis of Hybrid Renewable Energy Systems for European islands: Market Dynamics, Opportunities and Challenges - Antonia Papadaki; Nikolaos Savvakis; Nikolaos Sifakis; Georgios Arampatzis (Sustainable Futures)
European islands face energy challenges because of their geographical isolation and dependence on imported fuels. Despite the significant potential of renewable energy (RE), the extensive deployment of HRES faces economic, technical and regulatory restrictions. The scope of this study is to address the critical gap in understanding Hybrid Renewable Energy Systems (HRES) market dynamics by examining deployment, key challenges, and policy frameworks that restrict their usage. These steps will enhance energy independence, sustainability, and support the EU's transition to RE. HRES were aligned with island specific traits and islands were classified based on RES penetration, economic development, geospatial clustering and population and geographical size. The methodology followed was mixed, combining a comprehensive literature analysis with a structured survey of 50 industry experts, to examine the barriers and drivers impacting HRES deployment. Also, a SWOT analysis of HRES was conducted, identifying key strengths, weaknesses, opportunities, and threats influencing their adoption. The results showed that islands with strong regulatory framework and stakeholder engagement had higher HRES adoption. The weakly networked islands benefit the most from energy storage systems, whereas specific policy actions can improve energy security and reduce carbon emissions by up to 40 %. Simplified licensing procedures emerged as the most critical determinant of HRES adoption, with a rating of 4.6/5. In conclusion, this study provides a policy proposal for promoting HRES adoption on EU islands, recommending fit-for-purpose regulatory frameworks, finance approaches, and technology advancements.